PRESCRIPTION PATTERN OF DRUGS AND WHO PRESCRIBING INDICATORS USED IN ALCOHOLIC LIVER DISEASE PATIENTS IN A TERTIARY CARE TEACHING HOSPITAL IN NORTH EASTERN INDIA - VINAYAK S. JAMDADE,; ANURADHA MALIK,; SAMBASIVA RAO KOLATI,; DINESH REDDY,; MANGALA LAHKAR, (International Journal of Pharma and Bio Sciences, 2015)
Patients of alcoholic liver disease (ALD) attended the medicine department of Gauhati Medical College and Hospital (GMCH) with varieties of chief complaints like swelling of hind limb, hematemesis, abdominal distension and passing of starry black stools. The use of proton pump inhibitors, antioxidants, vitamins, laxatives, ulcer protective agents, cholagogues, corticosteroids, diuretics, antibiotics and hemorrheologic agents was very common for the treatment of ALD. The research was done to analyze the prescription pattern of drugs used in alcoholic liver disease patients’ in Gauhati Medical College and Hospital, Guwahati in North Eastern India. A prospective observational; unicentric study was conducted in the medicine department of GMCH during February 2014 to May 2014. Patients who were attending to medicine department were enrolled in the study as per selection criteria. The information on alcoholic liver disease prescriptions was recorded and pattern of drugs used for it was analysed. A total of 118 patients were included in this study in four months period and their prescriptions were analyzed. The total number of male patients was much higher than female patients. As single prescription, pantoprazole was found to be the most frequently prescribed drugs, whereas cefotaxime and sulbactum were the most frequently used drugs as combination therapy. As per Wold Heath Organization (WHO) prescribing indicators, the average number of drugs per encounter was 7.1. Moreover, percentage of drugs prescribed by generic name, percentage of encounters with an injection, percentage of encounters with an antibiotics and percentage of drugs prescribed from National List of Essential Medicine of India (NLEMI) 2011 were 37.77, 42.22, 22.22 and 55.55 respectively. This unicentric study, shows that pantoprazole 80 mg and 40 mg were found to be the most commonly prescribed drug followed by lactiol monohydrate and vitamin B supplements in an alcoholic liver disease. Moreover, all WHO prescribing indicator showed a deviation from the standard prescribing indicators values, except antibiotics which were prescribed within the standard limits.